(untitled) (Research, Society and Development, 2020)
This article comes from a PhD thesis which had as research question: "How external evaluations of basic education influence public educational policies and their effects on the performance of teachers and school managers." One such interference is associated with International Organizations such as the World Bank and UNESCO. Given this, this paper aims to make notes and reflections about the influences of international organizations in the national context regarding the elaboration and implementation of public policies for Basic Education. For the elaboration of the research it was used a qualitative approach based on the bases of the bibliographical and documentary research. The data analysis was based on Bardin (2011) and refined using the Policy Cycle approach proposed by Stephen Ball and Collaborators. As a result, it is well known that educational policies - funded and funded by International Organizations - can hardly find anything other than the education market. Thus, the propagation of neoliberal logic in Brazilian education is anchored in / by the interest of international capital. Faced with this scenario it is necessary to avoid “import educational packages" that ignore the brazilian contexts and its educational plans.